2018
DOI: 10.1242/jcs.218479
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical forces on cellular organelles

Abstract: The intracellular environment of eukaryotic cells is highly complex and compact. The limited volume of the cell, usually a few hundred femtoliters, is not only occupied by numerous complicated, diverse membranous and proteinaceous structures, these structures are also highly dynamic due to constant remodeling and trafficking events. Consequently, intracellular interactions are more than just opportunities to exchange molecules; they also involve components physically navigating around each other in a highly co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 66 publications
0
65
0
Order By: Relevance
“…To our knowledge, there are no previous findings reporting mitochondrial morphologic changes in different orientations in response to exercise. Nevertheless, it has been recently reported that mechanical forces can promote mitochondrial morphology changes leading to fragmentation (2, 50). The fact that we observed a down‐regulation of FIS1 and MFF gene expression led to the hypothesis that mitochondrial morphologic changes in response to HIHVT may occur in response to intramuscular forces by which mitochondria are getting squashed between muscle fibers.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are no previous findings reporting mitochondrial morphologic changes in different orientations in response to exercise. Nevertheless, it has been recently reported that mechanical forces can promote mitochondrial morphology changes leading to fragmentation (2, 50). The fact that we observed a down‐regulation of FIS1 and MFF gene expression led to the hypothesis that mitochondrial morphologic changes in response to HIHVT may occur in response to intramuscular forces by which mitochondria are getting squashed between muscle fibers.…”
Section: Discussionmentioning
confidence: 99%
“…could change the local mechanical properties at the constriction site[55], facilitating division. Finally, mitochondrial division has been observed to take place near replicating nucleoids[56] the presence of which might create 'rigid islands' that increase bending energies at adjacent constriction sites[57], making them more likely to divide according to our model. Such internal mechanisms could simultaneously control the positioning and fate of mitochondrial constrictions.…”
mentioning
confidence: 89%
“…This metabolic reprogramming is quite evident during stem cell transition from self-renewal to differentiation [151] and can be the result of the specific activated gene program. However, since the shift in the metabolism often precedes cell fate establishment, it may play a permissive or instructive role on cell commitment [152][153][154].…”
Section: Mechanotransduction In β-Cells: the Contribution Of Metabolismmentioning
confidence: 99%
“…All the three cytoskeletal components-actin, intermediate filaments, and microtubules-interact with mitochondria; they can act as rails to support mitochondrial movement, or they can control mitochondria shape, network organization, and confinement in subdomains with high metabolic demands [156][157][158]. Therefore, it is not surprising that biophysical forces, by modifying the cytoskeletal organization, can also remodel mitochondria [153].…”
Section: Mechanotransduction In β-Cells: the Contribution Of Metabolismmentioning
confidence: 99%